Rwanda : Poverty Reduction Strategy Paper; Progress Report. (IMF Staff Country Reports; Country Report, 2011)
Rwanda's Economic Development and Poverty Reduction Strategy (EDPRS) covers the period 2008-12 and provides a medium-term framework for achieving the country's long-term development aspirations as embodied in Rwanda Vision 2020, the seven-year Government of Rwanda (GoR) program, and the Millennium Development Goals. The economic cluster covers the macroeconomic and financial sector (energy, transport, information and communication technology (ICT) and Science, Technology and Innovation (STI), private sector development, and environment and natural resources management; and the social sector covers health, water and sanitation, education, social protection, and youth. The government cluster is also viewed.